2012
DOI: 10.26719/2012.18.4.402
|View full text |Cite
|
Sign up to set email alerts
|

Road rage and road traffic accidents among commercial vehicle drivers in Lahore, Pakistan

Abstract: Road rage and road traffic accidents increase the burden of morbidity and mortality in a population. A cross-sectional survey with convenience sampling was conducted among commercial vehicle drivers in Lahore, Pakistan (n = 901) to record their behaviours/experiences regarding road rage and road traffic accidents. Respondents were asked about incidents of shouting/cursing/rude gestures or threats to physically hurt the person/vehicle, by others or themselves, in the previous 24 hours or 3 months, and their inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
1
6
1
Order By: Relevance
“…In comparison to texting behind the wheel, angrily driving was five times more likely to result in a crash [40]. These findings of the current study are consistent with those of Shaikh et al (2012), who found that road rage was very common among the Pakistani commercial vehicle drivers [41]. Also, another study conducted on taxi drivers in South Africa showed that taxi drivers were statistically more likely to engage in aggressive driving behaviors than other drivers.…”
Section: Discussionsupporting
confidence: 89%
“…In comparison to texting behind the wheel, angrily driving was five times more likely to result in a crash [40]. These findings of the current study are consistent with those of Shaikh et al (2012), who found that road rage was very common among the Pakistani commercial vehicle drivers [41]. Also, another study conducted on taxi drivers in South Africa showed that taxi drivers were statistically more likely to engage in aggressive driving behaviors than other drivers.…”
Section: Discussionsupporting
confidence: 89%
“…On contrary, this prevalence of this study is higher than studies conducted in in Mekele, Ethiopia (the last three years' prevalence = 26.4%), 14 Ibadan Nigeria (in the last one-year prevalence =15.9%) among long-distance drivers 15 & drivers of public institutions in (since commencement= 16.2%), 16 Lahore Pakistan (in the last twelve months' prevalence = 12.4%) among commercial vehicle drivers 17 & UAE(United Arab Emirate), sultanate Oman (ever exposure to RTA= 44%) among road users. 18 The difference might be due to the type of study population involved, different study periods, the difference in the type of vehicles involved & the different study design used.…”
Section: Discussioncontrasting
confidence: 82%
“…It is estimated that the actual cases are much higher than the reported figures. It is because, every road accident does not get registered by the traffic police, as parties involved in such accidents resolve the conflicts on their own [26]. Results from the study suggest that with wall U-turns are more likely to encounter higher number and severe intensity of road crashes thus, causing to higher number of fatalities.…”
Section: Discussionmentioning
confidence: 79%